2007
DOI: 10.4049/jimmunol.179.12.8297
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between GATA-3 and the Transcriptional Coregulator Pias1 Is Important for the Regulation of Th2 Immune Responses

Abstract: Th2 cytokine expression is dependent on the transcription factor GATA-3. However, the molecular interactions of GATA-3 leading to Th2 cytokine gene activation have not been well characterized. Here, we reported a number of GATA-3 associated proteins in Th2 cells, and one of such proteins Pias1 functioned as a positive transcriptional coregulator for GATA-3. When overexpressed in Th2 cells, Pias1 enhanced the expression of IL-13, and to lesser degrees, IL-4 and -5. Conversely, Pias1 siRNA down-regulated the Th2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…C-maf regulates IL-4 production but is not required for production of other Th2 cytokines (43). Similarly, Pias1 increases IL-13 production without affecting IL-4 or IL-5 expression (44). We have shown that PU.1 decreases expression of many Th2 cytokines, but increases expression of CCL22, a chemokine associated with Th2 inflammation (8).…”
Section: Discussionmentioning
confidence: 99%
“…C-maf regulates IL-4 production but is not required for production of other Th2 cytokines (43). Similarly, Pias1 increases IL-13 production without affecting IL-4 or IL-5 expression (44). We have shown that PU.1 decreases expression of many Th2 cytokines, but increases expression of CCL22, a chemokine associated with Th2 inflammation (8).…”
Section: Discussionmentioning
confidence: 99%
“…GATA-3 associates with Ubc9 and the SUMO-E3 ligase PIAS1 in yeast two-hybrid assays, suggesting that sumoylation is possible; but studies focusing on PIAS1 suggest this may have the opposite effect as that seen with c-Maf (59). Overexpression of PIAS1 in DO11.10Ca −/− splenocytes enhances GATA-3 binding to the IL-13 promoter and increases IL-13 production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, distinct structural features of GATA3 are important for IL-13 production. A study showing that protein inhibitor of activated STAT1 (PIAS1) binds to GATA3 in T H 2 cells and controls IL-13 production but not IL-5 or IL-4 production indicates that distinct co-activators may be recruited for individual cytokines110.…”
Section: Structural Insights Into Gata3 Functionmentioning
confidence: 99%